PENGARUH BUDAYA PERUSAHAAN BERORIENTASI PASAR TERHADAP IMPLEMENTASI STRATEGI PEMASARAN PADA BANK NAGARI - Douval Douval; Sulastri Sulastri (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
This research aims to identify 1) The effect of internal cooperation and communication to marketing strategy implementation within Bank Nagari.2) The effect of driven to be the best to marketing strategy implementation within Bank Nagari 3) The effect of learning organisation to marketing strategy implementation within Bank Nagari 4) The effect of customer orientation to marketing strategy implementation within Bank Nagari5) The effect of competitor orientation to marketing strategy implementation within Bank Nagari. This research contains all of Bank Nagari’s employeeas populations and 95 among them were choosen as samples. Data were gathered by using interval scale quiestionnaires and results were analysed by using descriptive statistics and path analysis. The results showed that Internal cooperation and communication affects insignificantly positive to marketing strategy implementation (Coef 0,157 sig.0,126), Driven to be the best affects insignificantly positive to marketing strategy implementation (Coef 0.049 sig.0,503), Learning organisation affects significantly positive to marketing strategy implementation (Coef 0.244 sig.0,002), Customer orientation affects significantly positive to marketing strategy implementation (Coef 0.327 sig.0,000) and Competitor orientation affects significantly positive to marketing strategy implementation (Coef 0.231 sig.0,003). This research also adress some aspects to be continuesly improved by Management to maximize the level of exixtence of market oriented culture as well as marketing strategy execution within Bank Nagari. Keyword: Market oriented culture characteristics (internal cooperation and communication, driven to be the best, learning organisation, customer orientation and competitor orientation), marketing strategy implementation.